2017
DOI: 10.22146/jh.v29i3.24954
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Impoliteness in The Sociopragmatic Perspective

Abstract: The discrepancy of the study of linguistic politeness and impoliteness phenonema has been pronounced in the pragmatic study. However, up to this day the study of linguistic impoliteness, particularly based on culture-specific backgrounds has not been done. This research discusses the pragmatic manifestations of linguistic impoliteness. Through this research, a detailed description of how the manifestations and intentions of the linguistic impoliteness markers would be obtained. The data was gathered by using l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…The locational source of the research data is the daily utterances in the Javanese community, especially spoken by those living in Yogyakarta and around the researchers. Substantially, the source of the research data is the utterances spoken by the Javanese community in the location previously determined (Mahsun, 2005), containing the phatic function 'monggo' in the clearly-identified cultural and situational contexts (Rahardi, 2017c).…”
Section: Methodsmentioning
confidence: 99%
“…The locational source of the research data is the daily utterances in the Javanese community, especially spoken by those living in Yogyakarta and around the researchers. Substantially, the source of the research data is the utterances spoken by the Javanese community in the location previously determined (Mahsun, 2005), containing the phatic function 'monggo' in the clearly-identified cultural and situational contexts (Rahardi, 2017c).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the cooperation to make others equal can only be achieved when there is an ‗encounter' between them to cooperate. The writer's opinion is corroborated by Abercrombie that ‗ties of union' means union in encounter to build agreements (12).…”
Section: Review Of Literaturementioning
confidence: 97%
“…Linguists have not investigated phatic communion in the pragmatic perspective. Bousfield and Locher argued that there has been a discrepancy between the study of language impoliteness and language politeness since Fraser elaborated four major perspectives, namely: (1) the social norm review, (2) the conversational-maxim view, (3) the face-saving view, and (4) the conversational contract view (21), (12). It can be concluded that the study of linguistic phatic communion is left behind compared to studies on other pragmatic phenomena and it tends to be deserted by language researchers.…”
Section: Review Of Literaturementioning
confidence: 99%
“…However, the locational data source of cyberpragmatic research is in virtual communities that are very easily accessible from the clever schemes that are always in everyone's hands. The new era has turned out to be truly a change in Indonesian people's behavior, let alone the world community, in which people must not be separated from information and communication with smart mobile devices at any time (Rahardi, 2017b)up to this day the study of linguistic impoliteness, particularly based on culture-specific backgrounds has not been done. This research discusses the pragmatic manifestations of linguistic impoliteness.…”
Section: Introductionmentioning
confidence: 99%